The Evaluation of a Hip Hop and School Counselor Education Course - Ian P Levy; James Norris; LaNita Jefferson (Teaching and Supervision in Counseling, 2024)
The training of future school counselors to integrate school-based mental health resources has never been as important within a climate where US schools replicate the racial violence and fear we see nationally, at the expense of wellbeing. Fostering multicultural counseling competencies in school counselors are critical for their tackling of the challenges that historically marginalized and culturally diverse individuals, groups, and communities face. The purpose of this study was to assess the impact of a Hip Hop-based school counselor education course on the development of graduate student’s multicultural competence. Results from qualitative analysis of course assignments indicated that graduate school counseling students learned culturally responsive clinical skills, such as the use of Hip Hop lyrics in session, the facilitation of Hip Hop groups, and the use of varied Hip Hop group activities through their participation in this course. Additionally, pre- and post-course surveys showed positive changes in student’s multicultural self-efficacy.
Keywords: hip hop; counselor education; educator-counselor; culturally responsive; cultural competence